Ekperimentasi Metode Conceptual Understanding Procedures dan Mind Mapping Ditinjau dari Gaya Belajar - Mahmudah, Anis; Sutarni, Sri; Rejeki, Sri (Jurnal Varidika: Varia Pendidikan, 2015)
This study aims at evaluating: (1) the difference of studentsâ mathematics learning achievement viewed from two different learning methods, (2) the difference of studentsâ mathematics learning achievement viewed from different learning styles, (3) the effect of interaction between teaching methods and learning styles on studentsâ mathematics learning achievement. This study is a quantitative research with quasiexperimental research design. The population of this study is 210 students of 10thgrade of SMA MTA Surakarta. Two classes were chosen for the sample of this study by cluster random sampling. The first class was treated using Conceptual Understanding Procedures (CUPs) method and the second class was treated using Mind Mapping method. The data collection was conducted using test, questionnaire, and documentation. Morever, the data was analized using different number of cell analysis of variance with 5% significance level. The conclusion are: (1) there is difference on studentâs mathematics learning achievement viewed from two different learning methods, Conceptual Understanding Procedures (CUPs) a give better achievement than Mind Mapping, (2) there is no difference on studentsâ learning achievement viewed from different learning styles, (3) there is no effect of interaction between teaching methods and learning styles on studentsâ mathematics learning achievement.